Noble-metal-free Fe2P–Co2P co-catalyst boosting visible-light-driven photocatalytic hydrogen production over graphitic carbon nitride: The synergistic effects between the metal phosphides. (8th February 2019) - Cheng, Linhao; Xie, Sanmu; Zou, Yajun; Ma, Dandan; Sun, Diankun; Li, Zhihui; Wang, Zeyan; Shi, Jian-Wen
Abstract: Photocatalytic hydrogen evolution from water splitting driven by visible light is a promising approach to solve energy crisis and environmental problems, and noble-metal-free co-catalysts for boosting the hydrogen evolution reaction are highly desired. Herein, we explore a novel noble-metal-free Fe2 P–Co2 P co-catalyst for the first time to boost the photocatalytic performance of graphitic carbon nitride (g-C3 N4 ). The resultant Fe2 P–Co2 P/g-C3 N4 with optimum ratio exhibits a hydrogen production rate of 347 μmol h −1  g −1 in the absence of noble-metal co-catalyst, which is 87 times higher than that of pristine g-C3 N4 under the same conditions. The significant enhancement in the photocatalytic performance of Fe2 P–Co2 P/g-C3 N4 can be ascribed to the Schottky junction formed between Fe2 P–Co2 P and g-C3 N4, which produces a strong driving force for the transfer of electrons from g-C3 N4 to Fe2 P–Co2 P, promoting the separation and transfer of photogenerated electrons and holes. Furthermore, due to the synergistic effects between the two metal phosphides (Fe2 P and Co2 P), the Schottky junction in Fe2 P–Co2 P/g-C3 N4 can produce stronger driving force than that in Fe2 P/g-C3 N4 and Co2 P/g-C3 N4, resulting in the fact that the hydrogen production rate over Fe2 P–Co2 P/g-C3 N4 is much higher than that over Fe2 P/g-C3 N4 and Co2 P/g-C3 N4 . This work may shed light on the careful design of co-catalyst by utilizing the synergistic effect of different components. Highlights: A novel noble-metal-free FeCoP co-catalyst was developed for the first time. The resultant FeCoP/g-C3 N4 exhibits a hydrogen production rate of 347 μmol h −1  g −1 . The Schottky junction formed between FeCoP and g-C3 N4 facilitated electrons' transfer. The synergistic effects between Fe2 P and Co2 P can produce stronger driving force.